Securitization of Coastal Defense in The Delta Works Projects: Lesson learned for Indonesia - Maria Chris Lievonne; Fauzia Gustarina Cempaka Timur; Dr. Muhammad Hadianto (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2025)
The phenomenon of sea level rise, attributable to climate change, poses a significant threat to island nations and coastal regions, including Indonesia. Jakarta, a metropolitan area with a population of 10.684.946, is projected to experience substantial flooding, with estimates indicating that by 2050, one-third of the city may be submerged. In response to this impending threat, the Indonesian government has initiated developments in coastal defense. To identify appropriate measures for Indonesia, it is essential to reference the experiences of other nations, notably the Netherlands. The Netherlands was selected due to its extensive experience in coastal defense, particularly through its Delta program. The success of this initiative commenced in 1953 following a catastrophic flood that resulted in significant loss of life and property. The Delta Works project, which was undertaken as the initial response, engaged all societal levels and aimed to safeguard coastal areas and regions below sea level from future flooding incidents. This research employs qualitative methodologies and literature techniques, presenting findings in a descriptively narrative format through the lens of securitization theory. The objective of this study is to elucidate the Dutch measures in implementing the Delta program, with a specific focus on the Delta Works, and to extract lessons applicable to Indonesia, particularly within the Jakarta region, from the successful development of coastal defense initiatives. The findings indicate that the Netherlands established a national defense framework through the institutions of the Delta program. Key elements necessary for the success of coastal defense projects include community involvement, transparency, and a commitment to long-term engagement in the implementation of these initiatives.